2016
DOI: 10.2139/ssrn.2870680
|View full text |Cite
|
Sign up to set email alerts
|

Location Choice, Portfolio Choice

Abstract: Households hold nondiversified stock portfolios of firms headquartered near their city of residence. Explanations assign a causal role for proximity, either in generating an informational advantage or a familiarity bias. Empirical analyses assume households locate randomly, even though they optimally select a city. This selection is important since latent location factors might be correlated with latent demand for local stocks. Building on location choice models from urban economics, we develop a Heckman (1977… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Third, our paper is also related to studies on geographic location and portfolio choice (e.g., Bodnaruk, ; Branikas, Hong, & Xu, ; Christos & Wang, ; Coval & Moskowitz, , ; Ivkovic & Weisbenner, ; Kang & Stulz, ). For instance, Coval and Moskowitz (, ) found that mutual fund managers in the USA had a strong bias toward nearby companies.…”
Section: Introductionmentioning
confidence: 99%
“…Third, our paper is also related to studies on geographic location and portfolio choice (e.g., Bodnaruk, ; Branikas, Hong, & Xu, ; Christos & Wang, ; Coval & Moskowitz, , ; Ivkovic & Weisbenner, ; Kang & Stulz, ). For instance, Coval and Moskowitz (, ) found that mutual fund managers in the USA had a strong bias toward nearby companies.…”
Section: Introductionmentioning
confidence: 99%